Penerapan Model Pembelajaran Learning Cycle 7E untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 19 Makassar - Juacline Ermawani Saman; Nurhayani H. Muhiddin; Sitti Saenab (Universitas Negeri Makassar, 2025)
This research aims to determine: 1) Improvement in learning outcomes of class VIII students at SMPN 19 Makassar after being taught using the 7E learning cycle learning model, 2) Scores in the effect size category of using the 7E learning cycle learning model on improving learning outcomes for class VIII students at SMPN 19 Makassar , 3) Is there a significant difference in the learning outcomes of class VIII students at SMPN 19 Makassar before and after being taught using the 7E learning cycle learning model, 4) Is there no significant difference in the average score of improvement between class VIII I and class VIII K of SMPN 19 Makassar after being taught using the 7E learning cycle learning model. This type of research is Pre-Experimental Design research with a research design using One Group Pretest-Posttest Design. The population of all class VIII students at SMPN 19 Makassar consisting of 11 classes with a total of 348 people, the sample was selected using purposive sampling, with 2 classes, namely class VIII I totaling 31 people as the experimental class and class VIII K totaling 30 people as the replication class. The research instrument is in the form of learning outcome test questions. Data collection was carried out by giving a Pretest and Posttest. Data were analyzed using descriptive statistics and inferential statistics. Based on the results of the analysis, it was concluded that 1) The learning outcomes of students at SMPN 19 Makassar after implementing the 7E learning cycle model on the human digestive system material for class VIII I with an average score of 17.00 were in the medium category while the learning results for class VIII K with an average score of 15.13 which is in the medium category, 2) The level of results of the effect size analysis of students after implementing the 7E learning cycle learning model in class VIII I has an average of 2.27 which is in the strong effect category and class VIII K has an average of 2.59 which is in the strong effect category, 3) There is a significant increase in class VIII students at SMPN 19 Makassar before and after the implementation of learning cycle 7E, 4) There is no significant increase in the average N-Gain score for class students VIII I & VIII K SMPN 19 Makassar after implementing the 7E learning cycle learning model.